Japan's economic expansion - Allen, G. C. (Oxford University Press, 1965)
Contents: The author, who has been a student of the Japanese economy for some forty years, has based his book on information obtained from his recent investigation in Japan as well as on primary and secondary printed sources. A revised statistical appendix and bibliography are included